Chronic Kidney Disease in Children Within Five Years After Ifosfamide Chemotherapy for Childhood Cancer: A Dutch Pediatric Oncology Cohort Study - Lotte Pitlo; Francis S. P. L. Wens; Paulien A. M. A. Raymakers‐Janssen; Lianne M. Haveman; Johannes H. M. Merks; Martine van Grotel; Geert O. Janssens; Marta Fiocco; Marry M. van den Heuvel‐Eibrink; Gerrit van den Berg (Cancer Medicine, 2026)
ABSTRACT Introduction Children treated with ifosfamide seem to have an increased risk for developing chronic kidney disease (CKD) already within the first years following chemotherapy. However, studies investigating CKD prevalence in this specific phase are scarce. This study aimed to determine the prevalence, course, and determinants of CKD in ifosfamide‐treated children within the first five years after chemotherapy. Methods This cohort study included children treated with ifosfamide at the Princess Máxima Center for pediatric oncology in the Netherlands between 2015 and 2021. Chronic kidney disease was defined as decreased eGFR (< 90 mL/min/1.73 m 2 ) and/or proteinuria. Results This cohort consisted of 292 patients, with a median follow‐up duration of 30 months (IQR 7–46). The overall prevalence of CKD was 42.1% (123/292 patients), with 29 being at substantial risk of progression to kidney failure (eGFR < 60 mL/min/1.73 m 2 ). In 21 patients, CKD was reversible. A cause‐specific hazard model identified cumulative ifosfamide dose of 30–59.9 g/m 2 (HR cs 1.95, 95% CI 1.22–3.12) or > 60 g/m 2 (HR cs 4.09, 95% CI 2.08–8.02), increasing age at diagnosis (HR cs 1.12, 95% CI 1.06–1.18), and ≥ 2 episodes of acute kidney injury (AKI) during treatment (HR cs 3.81, 95% CI 2.24–6.46) as significant determinants. Conclusion With a prevalence of 42.1% within the first five years following ifosfamide administration, CKD is a common early complication, with varying severity; seven patients developed severe CKD (G4–G5). These findings highlight the importance of awareness and long‐term kidney function surveillance, especially in patients with a history of AKI.